KEANEKARAGAMAN VEGETASI HUTAN MANGROVE DI KECAMATAN KURAU KABUPATEN TANAH LAUT - Fithria, Abdi; Syam'ani, Syam'ani; Udiansyah, Udiansyah; Ruslan, Muhammad; Rezekiah, Arfa Agustina; Pramudya, Firman; Akbar, Pani; Diva, Achmad Arya; Fahmi, Hilman; Shiba, Yasinta Nur (Lambung Mangkurat University-Indonesia, 2024)
Kurau sub-district in Tanah Laut Regency is known to have a fairly extensive mangrove forest with great potential. One of the potentials is the variety of mangrove vegetation that grows in the forest. vegetation that grows in it. Knowing the diversity of mangrove forest species in Kurau sub-district aims to provide a scientific basis for in Kurau sub-district aims to provide a scientific basis for protecting and monitoring the forest. and forest supervision. The method used in the research is the technique of collecting data with purposive sampling and then analyzing with calculation of importance value index and Shannon-Wiener diversity index. Research The research was conducted based on the level of forest density consisting of high, medium and sparse forest density. high, medium, and sparse. The results obtained there are 11 types of vegetation that grow in mangrove forests and are dominated by the type of mangrove (Rhizophora mangle) which grows from seedling to tree level. Then followed by Rambai (Sonneratia caseolaris) and Api-api (Avicennia lanata). The level of species diversity in this mangrove forest is categorized as high with an index value of 5.5. high category with an index value of 5.46 for high forest density, 4.22 for medium forest density. While for sparse forest density included in the medium diversity category with a value of 2.34.